Estimating the burden of shigellosis in Thailand: 36-month population-based surveillance study - Pornthip Chompook; Seksun Samosornsuk; Lorenz von Seidlein; Supot Jitsanguansuk; Nunta Sirima; Sanit Sudjai; Prasitchai Mangjit; Deok Ryun Kim; Jeremy G. Wheeler; Jim Todd; Hyejon Lee; Mohammad Ali; et al. (The World Health Organization, 2005)
OBJECTIVE: To estimate incidence of shigellosis in the Kaengkhoi district, Saraburi Province, Thailand. METHODS: Population-based surveillance of shigellosis based in treatment centres. The detected rates of treated shigellosis were corrected for the number of cases missed due to the low sensitivity of microbiological culture methods and participants' use of health-care providers not participating in the study. FINDINGS: The overall uncorrected incidence of shigellosis was 0.6/1000 population per year (95% confidence interval (CI) = 0.5-0.8). The unadjusted incidence of treated shigellosis was highest among children less than 5 years old (4/1000 children per year; 95% CI = 3-6) and significantly lower among people aged > 5 years (0.3/1000 population per year; 95% CI = 0.2-0.5; P < 0.001). Adjusting for cases likely to be missed as a result of culture and surveillance methods increased estimates approximately five times. The majority of Shigella isolates (122/146; 84%) were S. sonnei; the rest were S. flexneri. Of the 22 S. flexneri isolates, the three most frequently encountered serotypes were 2a (36%), 1b (23%) and 3b (28%). A total of 90-95% of S. sonnei and S. flexneri isolates were resistant to tetracycline and co-trimoxazole. In contrast to S. sonnei isolates, more than 90% of the S. flexneri isolates were also resistant to ampicillin and chloramphenicol (P < 0.0001). CONCLUSION: Estimates of incidence of Shigella infection in the community are 10-fold to 100-fold greater than those found from routine government surveillance. The high prevalence of Shigella strains resistant to multiple antibiotics adds urgency to the development of a vaccine to protect against shigellosis in this region of Thailand.